New species, new records and complementary descriptions of two species of the genus Tenuipalpus Donnadieu (Acari: Tenuipalpidae) - Elgoni, Nasreldeen Ahmed; Kamran, Muhammad; Alatawi, Fahad Jaber (Zootaxa, 2024)
A new species of Tenuipalpus (Acari: Tenuipalpidae), Tenuipalpus farasanensis sp. nov., is described and illustrated based on female and male specimens collected from Salvadora spp. (Salvadoraceae). The discovery of this species leads to the proposal of a new species group, farasanensis, under Tenuipalpus sensu lato, characterized by six pairs of opisthosomal setae. In addition, four Tenuipalpus species, T. combreti Meyer, T. emeticae Meyer, T. tamarixi Mahdavi and Asadi, and T. viticola Al-Gboory, are reported from Saudi Arabia for the first time. Complementary descriptions of T. combreti and T. emeticae are also provided.